Legal Analysis Of The Resolution of The Trademark Plagiarisme Dispute Between MS Glow And PS Glow - Sulasno; Cindi Nur Febriani; Nada Salsabila Kusuma; Hasuri; Berthanila, Rethorika (Universitas Serang Raya, 2025)
A brand is an identification mark that is used to specifically differentiate between one product and another product. Trademarks are in the form of images, logos, names, words, letters, numbers, color schemes, two and/or three dimensions, sounds, holograms, or a combination of both. The factors above are to differentiate goods and/or services produced by individuals or legal entities in the context of trading goods and/or services. As technology and information develop, there are many disputes regarding brands. Like the MS Glow and PS Glow brand trophies which are widely discussed due to brand plagiarism trophies. The aim of this research is to find out how the Ms Glow and Ps Glow Trademark Dispute is resolved and legal protection efforts for the MS Glow and PS Glow trademarks. This research uses qualitative research methods and a normative type of research with a literature approach. Data search was carried out by reviewing and tracing related laws and regulations, books, literature, articles and documents regarding the study of trade secret issues. The results of this research were that settlements were carried out in two Commercial Courts. The lawsuit at the Medan Niaga District Court was won by Ms Glow, while the lawsuit at the Surabaya Niaga District Court was won by Ms Glow. The decision at the Surabaya Niaga District Court found that the Ms Glow brand used did not comply with the registered brand class